Reckoning with history : unfinished stories of American freedom - Downs, Jim, 1973-; Dunbar, Erica Armstrong; Hunter, T. K., 1956-2018; McCarthy, Timothy Patrick; Foner, Eric, 1943- (Columbia University Press, 2021)
" Reckoning with History brings together original essays from a diverse group of historians who consider how writing about the past can engage with the urgent issues of the present. The contributors-all former students of the distinguished Columbia University historian Eric Foner-explore the uses and politics of history through key episodes across a wide range of struggles for freedom. They shed new light on how different groups have defined and fought for freedom throughout American history, as well as the ways in which the ideal of freedom remains unrealized today. Covering a broad range of topics, these essays offer insight into how historians practice their craft in different ways and illuminate what it means to be a socially and politically engaged historian"--